Study on Simulation Performance of Solar Energy and Gas Heat Pump for Heating Supply - Hao, Hong; Mao, L.; Feng, G.; Wen, H. (2015)
© 2015 The Authors. Published by Elsevier Ltd. This paper introduces a new system named solar energy and gas heat pump, based on the solar heat pump system driven by electricity. The study established the models of the system according to the using of TRNSYS and SIMULINK. This paper mainly studies on the performance parameters of the new system, such as evaporation temperature, COP and heating capacity. At the same time, the paper makes a comparison of COP and PER between gas heat pump and solar energy heat pump, solar energy and gas heat pump. The results show that the evaporating temperature increases by 0.84°C when the thermal storage tank temperature increases by 1°C and the condensing temperature increases by 1.46°C when the condenser inlet temperature increases by 1°C. The COP of the new system can reach 4.76 and the primary energy ratio of the system is up to 1.96, which is superior to the other two systems obviously.